Kemampuan Guru Dalam Meningkatkan Public Speaking Siswa Melalui Ekstrakurikuler Khutbah Di MA Swasta Al- Ittihadiyah Mamiyai Bromo Kota Medan - Neliwati; Asmadi; Hidayatul Fikri Koto; Miftah Ilham Mazid (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Abstrak. This research delves into the role of teachers in the extracurricular activity of sermon training at the Private Islamic Senior High School Al-Ittihadiyah Mamiyai Bromo, particularly within the context of character formation, skill development, and the reinforcement of religious values among students. It is emphasized that the success of teachers in educating students in this activity relies heavily on their competence and skills in understanding, teaching, and implementing effective pedagogical approaches. Initial observations indicate several issues, such as the primary constraint of limited time and the inadequacy of evaluations measuring students' progress in sermon delivery. These challenges can impact the quality of learning and the students' achievements in the extracurricular program. Therefore, serious measures and comprehensive improvements are needed to enhance the effectiveness of the extracurricular sermon training activity and achieve religious education goals at Al-Ittihadiyah Mamiyai Bromo, Medan Area District, City of Medan.